Readiness of implementation of school-based assessment among the Malay language teachers in national schools - Chew, F.P.; Noriah, M. (2016)
This study aimed to identify the slcills readiness of Malay language teachers in National Schools in implementation of School Based Assessment (SBA) and identify whether there was any relationship between experiences of teaching among the Malay language teachers in National Schools with their skills in implementation of SBA. A questionnaire was used as an instrument in the study. The respondents consisted of 110 Malay language teachers in 35 National Schools located in the Klang Valley, Kuala Lumpur. Data analysis was carried out with the aid of the SPSS program. The results showed that the readiness of teachers in terms of skills affect the implementation of the SBA, while Pearson'r correlation analysis showed that there was significant correlation between the teaching experiences of the Malay language teachers in National Schools with their skills in the implementation ofSBA. The researchers also proposed some recommendations to make the SBA a success.